Social networks and the process of "globalization" - Georg Dürnecker; Fernando Vega-Redondo (University of Mannheim, Department of Economics, 2012)
We propose a stylised dynamic model to understand the role of social networks in the phenomenon we call "globalization." This term refers to the process by which even agents who are geographically far apart come to interact, thus being able to overcome what would otherwise be a fast saturation of local opportunities. A key feature of our model is that the social network is the main channel through which agents exploit new opportunities. Therefore, only if the social network becomes global (heuristically, it "reaches far in few steps") can global interaction be steadily sustained. To shed light on the conditions under which such a transformation may, or may not, take place is the main objective of the paper. One of the main insights arising from the model is that, in order for the social network to turn global, the economy needs to display a degree of "geographical cohesion" that is neither too high (for then global opportunities simply do not arise) nor too low (then the meeting mechanism displays too little structure for the process to take off). But if globalization does materialize, we show that it is a robust state of affairs that often arises abruptly as key parameters change. This occurs, in particular, as the rate of arrival of ideas rises, or when there is a high enough increase in the range at which the network transmits information.
urn:nbn:de:bsz:180-madoc-325453
Keywords: D83; D85; C73; O17; O43; 330; Social networks; Globalization; Search; Cooperation; Social Cohesion; Innovation